THE NAMES OF CITY IM COLONIAL BRAZIL. CONSIDERATIONS OFTER CAPTAINY THE RIO GRANDE DO NORTE - Teixeira, Rubenilson Brazão (Mercator, 2008)
The present paper is a reflection on different terms utilised to define urban centres in Brazil, especially, but not exclusively, along the colonial period. The Portuguese colonisers had specific names to designate their settlements, according to the political, economical, religious or military functions each one of them was supposed to achieve. Even though most of the expressions apply to the whole colony, they are explained in the context of the ancient captaincy of Rio Grande do Norte. The paper, an adapted excerpt from a doctoral thesis, deals firstly with the terms and expressions employed in Rio Grande do Norte, and secondly with the terminology related to the ancient Catholic missions to the Indians.